Microbial Detection and Antibiotic Susceptibility patterns of Clinical Isolates from Women With Urinary Tract Infection in AL-Nasiriyah City/Iraq - Jihad, Muna; Salih, Manal (University of Thi-Qar Journal of Science, 2024)
Urinary tract infections (UTIs) in women are one of the most common diseases affecting at different ages of the life. This study was aimed to investigate the uropathogenes in women with UTI and to test their antibiotic susceptibility pattern. A total of 150 urine samples were collected from patients women and healthy in Thi-Qar Province, southern Iraq, between December 2022 and March 2023.Urine samples were collected from each participant women and cultured on media, then identified by different laboratory methods such as characteristic of colony on culture media, Gram stain, biochemical tests and morphologic chromatic properties on Hi UTI chromogenic agar and confirmed by API 20E system. The majority of females (44%) were the age groups 25 to 34 years followed by the (34%) patients were age group from 15 to 24 years. Antibiotic susceptibility testing for bacteria species was performed using the Kirby,Bauer disc, diffusion technique. Out of 136 different isolates with noticeable growth were found in the urine sample after microbiological cultures were performed, bacteria species was represented (63.24%) more than Candida species which was (36.76%). The most frequent bacterium was Staphylococcus species (40.69%) followed by Escherichia coli (18.60%). These bacterial exhibited extremely resistance to antibiotics. Gram positive isolates showed the highest resistant against Amoxicillin-clavulanate (100%), Ampicillin (100%), Oxacillin (100%), and Trimethoprim (91.66%), on the other hand Gram negative bacteria also showed the highest resistance against Amoxicillin-clavulanate (100%), Piperacillin (100 %), and both Ceftazidime and Nitrofurantoin (86.36 %). Other antibiotics showed different results by different bacterial species.